Design of an analytical model of municipal employment distribution - Manzanares-Gutiérrez, Ángel; García-Macía, Basilia (Acciones e Investigaciones Sociales, 2025)
This research addresses the problem of economic and social inequality derived from the concentration of employment in specific areas. Taking the municipality of Elche as a case study, an analytical model is proposed to evaluate this distribution and offer solutions to promote a more equitable economic development. The general objective of this study is to design an analytical model to understand the distribution of employment at the municipal level, with specific objectives that include the identification of areas with high economic concentration, the analysis of sectoral diversity based on zip codes, and the formulation of recommendations for sustainable economic development. Methodologically, the study uses the Standardized Location Coefficient (SLC) to analyze data from the SABI INFORMA database on the distribution of companies and employment in Elche. This includes the collection of data from 12.960 companies with the application of a rigorous filter to ensure its validity. The results indicate a diverse economic distribution in Elche, with a notable concentration in Elche Parque Industrial, characterized by leather and footwear industries and building services. Both areas of high concentration and significant business diversification have been identified. In practical terms, the suggested model is crucial for economic planning. For Elche, it is recommended to promote business creation, boost innovation and improve local infrastructure. Specific strategies include investing in education, supporting economic diversification and promoting sustainable tourism to support economic growth in a more balanced and sustainable way.